Systemic immune-inflammation states in US adults with seropositivity to infectious pathogens: A nutrient-wide association study - Xie, He; Halimulati, Mairepaiti; Dou, Yuqi; Zhang, Hanyue; Jiang, Xiaowen; Peng, Lei (Journal of parenteral and enteral nutrition, 2025)
Background Limited understanding exists regarding the association between daily total dietary nutrient intakes and immune-inflammation states in US adults exposed to various pathogens. This study sought to examine the correlation between nutrient intakes and immune-inflammation indicators and to assess their performance in distinguishing immune-inflammation states. Methods This study was derived from the National Health and Nutrition Examination Survey (NHANES), which included 33,804 participants aged 20 years or older between 2005 and 2018. Multivariable linear regression and restricted cubic spline regression were conducted to evaluate the association between nutrient intakes and immune-inflammation indicators. Receiver operating characteristic curve analysis was performed to evaluate the discriminatory performance of identified nutrients for various immune-inflammation states measured by the systemic immune-inflammation index (SII). Results Ten key nutrients were significantly associated with immune-inflammation responses, including calcium, saturated fatty acid (SFA) 4:0, SFA 6:0, SFA 12:0, SFA 14:0, SFA 16:0, vitamin B2, total SFAs, retinol, and lutein + zeaxanthin, which show potential as dietary indicators. The area under the curve for discriminating various immune-inflammation states was improved by at least 0.03 compared with a model that included only covariates, with all P values <0.05 in the Delong tests, indicating a significant enhancement in model performance. Conclusions Ten nutrients, including calcium, various SFAs, vitamin B2, retinol, and lutein + zeaxanthin, exhibit significant association with SII and potential as dietary indicators for distinguishing between different immune-inflammation states in US adults with seropositivity to various viruses.